SPE Reservoir Simulation Symposium 1999
DOI: 10.2118/51931-ms
|View full text |Cite
|
Sign up to set email alerts
|

Nested Gridding and Streamline-Based Simulation for Fast Reservoir Performance Prediction

Abstract: This paper was prepared for presentation at the 1999 Reservoir Simulation Symposium, held in Houston, Texas, 14-17 February 1999.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 13 publications
1
40
0
1
Order By: Relevance
“…Upscaling methods offer an opportunity to reduce the size of the problem by decreasing the spatial resolution needed to adequately represent the simulation problem. As stated by de Marsily et al (2005) and demonstrated by several authors (e.g., Renard and de Marsily 1997;Ewing 1998;Gautier et al 1999), the goal of upscaling is to average the fine-scale properties such that flow calculations made at the upscaled level using the upscaled parameters provide a solution as close as possible to the one that could have been calculated in a high-resolution simulation on the finer grid with the original parameter values. Thus, the solution to this problem may lie in the development of appropriate upscaling methodologies.…”
Section: Models One Approach Is To Incorporate Only the Large-scale mentioning
confidence: 99%
“…Upscaling methods offer an opportunity to reduce the size of the problem by decreasing the spatial resolution needed to adequately represent the simulation problem. As stated by de Marsily et al (2005) and demonstrated by several authors (e.g., Renard and de Marsily 1997;Ewing 1998;Gautier et al 1999), the goal of upscaling is to average the fine-scale properties such that flow calculations made at the upscaled level using the upscaled parameters provide a solution as close as possible to the one that could have been calculated in a high-resolution simulation on the finer grid with the original parameter values. Thus, the solution to this problem may lie in the development of appropriate upscaling methodologies.…”
Section: Models One Approach Is To Incorporate Only the Large-scale mentioning
confidence: 99%
“…Since the pressure equation is elliptic, a coarse grid can be used to solve it. It was introduced by Ramiˊe and Killough (1991) and has been used for two-phase flow by Guèrillot and Verdière (1995), and Gautier et al (1999).…”
Section: Dual Mesh Methodsmentioning
confidence: 99%
“…However, the permeability of the coarse cells must be evaluated dynamically by flow calculations so that the upscaled models produce simulation results adequately close to the fine grid models. Streamline simulation is suitable both for designing non-uniform grid configuration aligned with streamlines 13) and for validation of the upscaled models readily visualizing streamlines 14) . We have developed a technique for the upscaling application implementing full-tensor permeability and non-orthogonal grids.…”
Section: Upscalingmentioning
confidence: 99%